2018
DOI: 10.1039/c8ra05654d
|View full text |Cite
|
Sign up to set email alerts
|

The production of tyramineviathe selective hydrogenation of 4-hydroxybenzyl cyanide over a carbon-supported palladium catalyst

Abstract: Tyramine hydrogen sulphate is produced via the heterogeneously catalysed selective hydrogenation of 4-hydroxybenzyl cyanide within a three-phase reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Among the precious metals, palladium is the most frequently used heterogeneous catalyst in the hydrogenation of nitriles, exclusively in supported form: on activated carbon [46][47][48][49][50][51][52][53], on alumina [51,52,[54][55][56][57][58][59][60][61][62], on MCM-41 [63] or on silica [64].…”
Section: Precious Metal Catalysts 31 Hydrogenations Over Palladiummentioning
confidence: 99%
“…Among the precious metals, palladium is the most frequently used heterogeneous catalyst in the hydrogenation of nitriles, exclusively in supported form: on activated carbon [46][47][48][49][50][51][52][53], on alumina [51,52,[54][55][56][57][58][59][60][61][62], on MCM-41 [63] or on silica [64].…”
Section: Precious Metal Catalysts 31 Hydrogenations Over Palladiummentioning
confidence: 99%
“…Whilst there are several instances where hydrogenolytic removal of a functional group is undesirable, such as the hydrogenolysis of benzylamine to yield toluene, 19,20 there are occasions where no hydrogenolysis of the amine functionality is observed. 21 Adding a further degree of complication, there are instances where the selective hydrogenolysis of one functional group in the presence of another is required. 21 The occurrence or absence of a hydrogenolysis step has previously been rationalised, primarily by Scheme 1 Two-step nitrile hydrogenation to the primary amine proposed by Sabatier et al 6 work undertaken by Maschmeyer et al, 17 which suggested that it is the positioning of the heteroatom with respect to the aromatic group which dictates the viability of the process.…”
Section: Introductionmentioning
confidence: 99%
“…21 Adding a further degree of complication, there are instances where the selective hydrogenolysis of one functional group in the presence of another is required. 21 The occurrence or absence of a hydrogenolysis step has previously been rationalised, primarily by Scheme 1 Two-step nitrile hydrogenation to the primary amine proposed by Sabatier et al 6 work undertaken by Maschmeyer et al, 17 which suggested that it is the positioning of the heteroatom with respect to the aromatic group which dictates the viability of the process. Recent work by McAllister and co-workers regarding the hydrogenation of 4-hydroxybenzyl cyanide supports this assertion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations